Evaluation of the Data Quality of Digital Elevation Models in the Context of Inspire - Chudý, Radoslav; Iring, Martin; Feciskanin, Richard (GeoScience Engineering, 2013)
The contribution deals with the evaluation of the quality of geographic information in accordance with the ISO standards from the family of ISO 19100. The quality assessment was carried out on a sample of the data of the digital elevation model of the Slovak republic – DMR3. The selected data quality elements and sub-elements were evaluated using measures defined in the INSPIRE data specification for Elevation.